Facebook as a Case Study: Exploring Da‘wah on Social Media in Southwestern Nigeria - Oladele, Ibrahim Abolaji; Fahm, AbdulGafar Olawale (Jurnal Ilmiah Ilmu Ushuluddin, 2024)
This study investigates the practice of da’wah (Islamic propagation) on social media in southwestern Nigeria, focusing specifically on Facebook. While previous research has examined da’wah through traditional media, little attention has been given to the emerging role of social media networks. Using historical, descriptive, and analytical methods, the research explores the challenges associated with da’wah on social media in Yorubaland, highlighting the absence of regulation in the new media. This lack of regulation has allowed unqualified and unprofessional da’wah presenters to flourish, resulting in controversial content and unguarded behavior. The study reveals that many renowned scholars and ducats in the six southwestern states of Nigeria have embraced social media, particularly Facebook, as an effective platform for disseminating their da’wah activities to a virtual audience. To ensure organized and result-oriented da’wah in the cyberspace of southwestern Nigeria, the research recommends the establishment of a regulatory framework to address the excesses of virtual du’at.